THE NECESSARY TO LEGISLATE “ZERO - HOUR CONTRACT” IN VIETNAM - Phạm Huy Tiến (Tạp chí Khoa học Đại học Đà Lạt)
The “Zero-hour contract” (a kind of labor contract) has had an impact on the labor market in England.  “Zero-hour contract” is widely practiced in Vietnam although the law has not caught up to this change.  This paper will mention the demands and the experiences of shaping “Zero-hour contract” into law.